1994
DOI: 10.3181/00379727-205-43690
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and Estradiol Interaction in the Regulation of Rat Uterine Weight and Estrogen Receptor Concentration

Abstract: Autologous down-regulation of hormone receptors has been shown for several steroid hormones. We have previously shown estradiol (E2) regulates estrogen receptor (ER) in ovariectomized (OVX) rats. These studies have been extended to investigate the interaction between progesterone (P) and E2 in the regulation of ER and uterine weight. We implanted Silastic capsules containing varying concentrations of E2 (0.0005 mg E2/ml to 5.0 mg E2/ml of sesame oil) into adult female Sprague-Dawley rats one week after OVX. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Although our study did not directly measure estrogen levels in plasma, ovariectomized animals demonstrated a significant loss in uterine weight, which in the past has been used as a reliable measure of estrogen deprivation at the end-organ site [34, 35, 36]. Our study may have, to some extent, underestimated the effect of estrogen on the CBF of control animals, insofar as select animals may have been examined at estrus.…”
Section: Discussionmentioning
confidence: 78%
“…Although our study did not directly measure estrogen levels in plasma, ovariectomized animals demonstrated a significant loss in uterine weight, which in the past has been used as a reliable measure of estrogen deprivation at the end-organ site [34, 35, 36]. Our study may have, to some extent, underestimated the effect of estrogen on the CBF of control animals, insofar as select animals may have been examined at estrus.…”
Section: Discussionmentioning
confidence: 78%
“…A down regulation of steroid receptors (ER and progesterone receptor-binding activity) by oestrogen treatment has been reported in sheep uteri (Meikle et al, 2000), and the authors suggested that this down regulation is a mechanism to limit hormone action in the target cells. An oestrogen down regulation of ERS1 expression was also found in rat uteri, and the regulation is dose dependent, as demonstrated by the stimulating or inhibitory effects of low or high doses of oestrogens, respectively (Medlock et al, 1994).…”
Section: Adrenal Weightmentioning
confidence: 88%
“…Dissociation constants (Kd, nM) for cytosolic ER were similar (mean ± SEM: 0.31 ± 0.05, n = 16), except in Group V, which had higher values (1.45 ± 0.21, n = 4; P < 0.05). An increase in ER Kd values after E2 treatment has been found previously in rat uteri [21], but the biological implication of these differences in binding affinity is not clear. The affinity for cytosolic PR was similar in all groups (0.65 ± 0.07 nM, n = 20).…”
Section: Enzyme Immunoassay (Eia) Of Er Proteinmentioning
confidence: 90%